Battered granny or spontaneous fractures? A legal dilemma. Issue 840 (October 1995) - Connolly, V.; McConnell, A. A.; McGarrity, G.
Abstract : A 70-year-old woman was admitted from a local nursing home with extensive bruising and bilateral hip discomfort. The referring doctor had reported the possibility of elder abuse to the police. Full examination showed that osteomalacia, precipitated by a poor diet and lack of exposure to sunlight, was sufficient to explain the patient's condition. Caution is recommended in diagnosing elder abuse until other possibilities have been excluded.